Improving Upper Limb Spasticity in Patients with Stroke by Electroacupuncture Therapy: a Pre- and Post-Treatment Study - Sung Min Lim; Eunji Go; Jungsup Lee; Go Eun Lee; Eun Joo Kim; Chihyoung Son (Medical Association of Pharmacopuncture Institute, 2023)
Background : Post-stroke upper limb spasticity (PS-ULS) causes a decline in the quality of life of patients by reducing their ability to perform normal daily activities.Objectives: We performed pre- and post-treatment analyses of the changes in stroke patients with ULS following constant electroacupuncture therapy (EAT). Methods : Thirty patients with PS-ULS underwent 12 sessions of EAT over 4 weeks. After performing acupuncture therapy at four acupoints on the affected arm (LI11, LI10, LI4, and TE5), electrostimulation (60 Hz) was performed for 20 min. The modified Ashworth scale (MAS) and the Fugl-Meyer assessment of the upper extremity (FMA-UE) were measured as the outcome variables. Results : Following EAT, there was a significant decrease in the elbow MAS score (p < 0.001), a significant decrease in the wrist MAS score (p < 0.01), and a significant increase in the FMA-UE score (p < 0.001). Adverse events related to EAT were not reported. Conclusion : EAT decreased upper limb spasticity and improved functional recovery at the elbow and wrist. Large-scale and rigorous clinical trials are needed to verify the efficacy of EAT.